Polemics of The Virtual Da’wah Hyperreality in Parepare City - Syam, Muhammad Taufiq; Nurhikmah, Nurhikmah; Kasman, Suf (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2024)
Preachers in Parepare City have utilized social media to deliver da'wah messages, but on the other hand conventional preachers still think that da'wah on social media has not supported the effectiveness of da'wah. Therefore, this research will analyze the hyperreality of virtual da'wah which has an impact on the polemic in interpreting the professionalism of preachers in Parepare City. This research employs a descriptive qualitative method using a case study approach to analyze and facilitate the narrative presentation of observation and interview results that have sparked debates regarding the use of social media by preachers in Parepare City for preaching purposes. The results of this study show various forms of da'wah transformation in social media, a description of the hypperality of da'wah in social media and cognitive dissonance which is the cause of the polemic of preachers in Parepare City. The implications of this research will show that the collaboration between conventional da'wah and the use of social media is needed in order to improve the professionalism of preachers, so as to minimize the occurrence of polemics in the use of da'wah media.